2021
DOI: 10.1371/journal.pone.0249861
|View full text |Cite
|
Sign up to set email alerts
|

Faecalibacterium prausnitzii increases following fecal microbiota transplantation in recurrent Clostridioides difficile infection

Abstract: Objective Fecal microbiota transplantation (FMT) is a highly effective treatment for Clostridioides difficile infection (CDI). However, the fecal transplant’s causal components translating into clearance of the CDI are yet to be identified. The commensal bacteria Faecalibacterium prausnitzii may be of great interest in this context, since it is one of the most common species of the healthy gut microbiota and produces metabolites with anti-inflammatory properties. Although there is mounting evidence that F. pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…We found clustering of the main protective species within the families Lachnospiraceae, Bacteroidaceae, and Oscillospiraceae. For example, F. prausnitzii , a beneficial human gut microbe touted as a candidate for next-generation probiotics 37 , was found to have reduced abundance in CDI patients, which was restored after FMT 38 . Interestingly, we have also identified a protective strain of the species Dorea longicatena, which is a component of a defined bacterial consortium (VE303) with encouraging Phase 2 clinical data, consisting of eight, nonpathogenic, nontoxigenic, commensal strains of Clostridia 39 .…”
Section: Discussionmentioning
confidence: 99%
“…We found clustering of the main protective species within the families Lachnospiraceae, Bacteroidaceae, and Oscillospiraceae. For example, F. prausnitzii , a beneficial human gut microbe touted as a candidate for next-generation probiotics 37 , was found to have reduced abundance in CDI patients, which was restored after FMT 38 . Interestingly, we have also identified a protective strain of the species Dorea longicatena, which is a component of a defined bacterial consortium (VE303) with encouraging Phase 2 clinical data, consisting of eight, nonpathogenic, nontoxigenic, commensal strains of Clostridia 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium is reduced in gut dysbiosis, in IBD, in obesity, in diabetes, etc. [ 96 ]. Lachnospiraceae is protective against CDI [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that stable Faecalibaterium colonization following FMT may play a crucial role in UC remission by alleviating intestinal inflammation. Of note, a recent study also found that FMT increases the relative abundance of F. prausnitzii in patients with recurrent CDI, and this microbial shift remains several months later [ 30 ]. However, the exact anti-inflammatory mechanism of Faecalibacterium remains unknown in these patients.…”
Section: Discussionmentioning
confidence: 99%